Systematic review with meta‐analysis: enteral nutrition therapy for the induction of remission in paediatric Crohn's disease. Issue 7 (16th August 2017) - Swaminath, A.; Feathers, A.; Ananthakrishnan, A. N.; Falzon, L.; Li Ferry, S.
Abstract: Background: Despite potential adverse‐events in a paediatric population, corticosteroids are used to induce remission in paediatric Crohn's disease. Exclusive enteral nutrition also induces remission, but is infrequently used in the USA because corticosteroids are considered the superior therapy. New data have become available since the publication of the most recent meta‐analysis in 2007. Aim: To see if current literature supports the use of EEN versus CS in paediatric populations. Methods: All studies with comparator arms of exclusive enteral nutrition and an exclusive corticosteroids, with remission clearly defined were identified by searching eight online databases. Results: Of 2795 identified sources, nine studies met our inclusion criteria. Eight of these (n = 451), had data that could be abstracted into our meta‐analysis. Exclusive enteral nutrition was as effective as corticosteroids in inducing remission (OR = 1.26 [95% CI 0.77, 2.05]) in paediatric Crohn's disease. There was no difference between Exclusive enteral nutrition and corticosteroids efficacy when comparing newly diagnosed Crohn's (OR = 1.61 [95% CI .87, 2.98]) or relapsed (OR = 0.76 [95% CI .29‐1.98]). Intestinal healing was significantly more likely among patients receiving Exclusive enteral nutrition compared to corticosteroids (OR = 4.5 [95% CI 1.64, 12.32]). There was no difference in the frequency of biomarker normalisation including CRP (OR = 0.85 [95% CI .44, 1.67]) and faecal calprotectin (OR 2.79 [95% CI .79‐10.90]). Conclusions: There is no difference in efficacy between exclusive enteral nutrition and corticosteroids in induction of remission in Crohn's disease in a paediatric population. Exploratory analyses suggest that a greater proportion of patients treated with exclusive enteral nutrition achieved mucosal healing. Abstract : Linked Content This article is linked to Dai et al and Feathers et al and Logan et al and Feathers et al papers. To view these articles visithttps://doi.org/10.1111/apt.14337, https://doi.org/10.1111/apt.14359, https://doi.org/10.1111/apt.14351 andhttps://doi.org/10.1111/apt.14360 .